Intervalence plasmons in boron-doped diamond - Souvik Bhattacharya; Jonathan Boyd; Sven Reichardt; Valentin Allard; Amir Hossein Talebi; Nicolò Maccaferri; Olga Shenderova; Aude L. Lereu; Ludger Wirtz; Giuseppe Strangi; R. Mohan Sankaran (Nature Communications)
Abstract Doped semiconductors can exhibit metallic-like properties ranging from superconductivity to tunable localized surface plasmon resonances. Diamond is a wide-bandgap semiconductor that is rendered electronically active by incorporating a hole dopant, boron. While the effects of boron doping on the electronic band structure of diamond are well-studied, any link between charge carriers and plasmons has never been shown. Here, we report intervalence plasmons in boron-doped diamond, defined as collective electronic excitations between the valence subbands, opened up by the presence of holes. Evidence for these low-energy excitations is provided by valence electron energy loss spectroscopy and near-field infrared spectroscopy. The measured spectra are subsequently reproduced by first-principles calculations based on the contribution of intervalence band transitions to the dielectric function. Our calculations also reveal that the real part of the dielectric function exhibits a crossover characteristic of metallicity. These results suggest a new mechanism for inducing plasmon-like behavior in doped semiconductors, and the possibility of attaining such properties in diamond, a key emerging material for quantum information technologies.